2005
DOI: 10.1097/01.ju.0000169457.08207.4b
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Functional and Urodynamic Results of 50 Patients Receiving a Modified Sigmoid Neobladder Created With a Short Distal Segment

Abstract: This modified sigmoid neobladder offers good daytime continence with low post-void residual and adequate daytime micturition frequency. Nighttime continence is poor. The presence of high intrareservoir pressures did not impair renal function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
29
2
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(38 citation statements)
references
References 19 publications
6
29
2
1
Order By: Relevance
“…The reduced level of consciousness during nighttime makes it impossible to increase the muscle tonus. In contrast to other studies, we could not find a higher pressure in the sigmoid pressure compared to the ileal neobladder [17] . Contrary to other studies, pressure values were less in the sigmoid bladder group and capacity was higher.…”
Section: Discussioncontrasting
confidence: 56%
“…The reduced level of consciousness during nighttime makes it impossible to increase the muscle tonus. In contrast to other studies, we could not find a higher pressure in the sigmoid pressure compared to the ileal neobladder [17] . Contrary to other studies, pressure values were less in the sigmoid bladder group and capacity was higher.…”
Section: Discussioncontrasting
confidence: 56%
“…Although nighttime continence rates and voiding intervals in our study are better than [16,18,19,20,21] or similar to [22,23] other techniques reported in the literature, nocturnal incontinence remains a noticeable problem in bladder substitution patients. After urinary bladder removal during radical cystectomy, loss of filling sensation and destruction of feedback mechanisms are naturally expected.…”
Section: Discussionmentioning
confidence: 52%
“…The most frequent complication reducing quality of life of patients is incontinence, mostly occurring at night. The incidence of daily incontinence is 0-65%, while the nocturnal incontinence is between 3%, 5% and 97% [4,[7][8][9][10][11][12][13]. The reasons of this significant fluctuation can be explained by different follow-up periods, different explanation of the term 'continence', and by the dissimilar type of orthotopic urine reservoir.…”
Section: Introductionmentioning
confidence: 79%
“…Furthermore, there was an insignificant increase observed after a followup of 0.5-2 years; however after this period there was no increase detected. In the case of sigmoid neobladder, Laguna [11] detected a stabilized capacity of neobladder (about 300 ml) after a follow-up of 3 months to 5 years. In addition, Burkhard [28], who performed a urodynamic examination 9 months and 5 years separately after the surgery, could not detect increase in bladder capacity either.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation